2021
DOI: 10.1172/jci.insight.139813
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of CF rabbits generated by CRISPR/Cas9-mediated disruption of the CFTR gene

Abstract: Existing animal models of cystic fibrosis (CF) have provided key insights into CF pathogenesis but have been limited by short life spans, absence of key phenotypes, and/or high maintenance costs. Here, we report the CRISPR/Cas9-mediated generation of CF rabbits, a model with a relatively long lifespan and affordable maintenance and care costs. CF rabbits supplemented solely with oral osmotic laxative had a median survival of ~ 40 days and died of gastrointestinal disease, but therapeutic regimens directed towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 84 publications
4
40
0
Order By: Relevance
“…Intestinal obstruction is the primary cause of mortality in CF rabbits [ 12 ], as exampled in Figure 2 . The proximal colon of CF rabbits is often dilated, and the distal colon presents a paucity of stool pellets ( Figure 2 A), which are not observed in WT animals ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intestinal obstruction is the primary cause of mortality in CF rabbits [ 12 ], as exampled in Figure 2 . The proximal colon of CF rabbits is often dilated, and the distal colon presents a paucity of stool pellets ( Figure 2 A), which are not observed in WT animals ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, compared to the mouse model, CF rabbits are large, making many experimental procedures more practical. Importantly, rabbit airway epithelial cells responded to CFTR modulator drug VX770 in a similar manner as human airway epithelial cells do, supporting the use of these animals in preclinical studies for CF [ 12 ].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In 2020, Xu et al (2020) reported the production of CF rabbit models by CRISPR/Cas9. CF rabbits manifest many typical disease phenotypes, including and beyond those observed in CF mice.…”
Section: Gene Edited Rabbits For Translational Studies Of Cystic Fibrosismentioning
confidence: 99%